Carbohydrate supplementation improves stroke performance in tennis - Vergauwen, L.; Brouns, F.; Hespel, P. . (Medicine & Science in Sports & Exercise, 1998)
The effect of carbohydrate supplementation on stroke quality during prolonged simulated tennis match-play was investigated. Well-trained tennis palyers reported to the test center three times. At each occasion they performed a pretest, consisting of the leuven Tennis Performance Test (LTPT) and a shuttle run (SHR), which they repeated (posttest) after a 2-h strenuous training session. Throughout the test session, they received in a double blind random order either a placebo drink (P), a carbohydrate solution (0.7 gxkg(-1) BWxh(-1); CHO), or CHO plus a dose of caffeine (5 mg per kg BW). Stroke quality was evaluated during the LTPT by means of measurements of error rate, ball velocity, precision of ball placement, and a velocity-precision (VP) and a velocity-precision-error (VPE) index. Pretest scores were similar during P and CHO. During P, compared with the pretest, stroke quality during the posttest deteriorated (P < 0.05) both for the first service and strokes during defensive rallies and for SHR performance. However, compared with P, the increase in error rate and number of nonreached balls indefensive rallies was smaller (P < 0.05) during CHO. Similarily, CHO attenuated (P < 0.05) the increase in error rate and the decrease in both the VP (P < 0.1) and VPE (P < 0.05) indices for the first service upon fatigue. Furthermore, CHO improved posttest SHR performance. Stroke quality and SHR time were similar during CHO alone and during combined CHO plus caffeine administration, both for the pretest and for the pretest and for the posttest. It is concluded that CHO supplementation improves stroke quality during the final stages of prolonged tennis play. The data prove that CHO intake may facilitate the maintenance of physical quality during long-lasting intermittent exercise to fatigue.